Media Live Streaming Berbasis Raspberry Pi Pada Perguruan Tinggi Raharja - Reynald Saevana Aria; Angi Nursetia Putra; Denny Andreansyah Putra (UNIVERSITAS RAHARJA, 2017)
Higher Education Prog is a university that focuses konsestrasi in the field of computer and technology, but in the field of penyampaikan information to students remains less efektik because they still use a paper or poster is attached to the wall magazine (Magazine Wall) and his appearance did not attract the students to see and listen information contained campus. The need for an innovation to renew methods penyampaikan user information into a digital form. The authors mebuat Broadcast media based information tool Raspberry Pi utilizing campus facilities like television to show some internal information campuses and as a forum to showcase the work of the Student Video Mavib to display to the Personal Prog.